COAPPROXIMATION IN PROBABILISTIC NORMED SPACES - Khorasani, A.; Moghaddam, M. A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
In this article, we studied the best coapproximation in probabilistic 2-normed spaces. We defined the best coapproximation on these spaces and generalized some definitions such as set of best coapproximation, P_b-coproximinal set and P_b-coapproximately compact and orthogonality relative to any set and proved some theorems about them.